Die Syntax der "Pis'ma russkogo putešestvennika" von N. M. Karamzin - Sauberer, Gabriele (Slavistische Beitraege, 1999)
N.M. Karamzin's "Pis'ma russkogo putešestvennika" (hereinafter PRP) occupy a special place in the history of Russian language and literature. Since their publication as a continuation novel in "Moskovskiy Žurnal" from 1791-1792 (in the following MŽ 1) they are considered both the first realization of the "novyj slog" (new language / new style) as well as the beginning of Russian sentimentalism. Both assumptions are controversial. The present work should contribute to the clarification of contentious questions by providing a detailed description of the syntactic facts in the main work of Karamzin for the first time.